Pengaruh Sosialisasi Pasar Modal dan Persepsi atas Risiko terhadap Minat Investasi Mahasiswa di Pasar Modal: Kata Kunci: Sosialisasi Pasar Modal, Persepsi Atas Risiko, Minat Investasi Mahasiswa di Pasar Modal - Dewi Kusuma Wardani; Supiati . (Jurnal Akuntansi, 2020)
This study aims to examine whether capital market socialization and risk perception affect student investment interests in the capital market. This research method uses quantitative descriptive methods and primary data. This study sampled 70 students from the Faculty of Economics at Sarjanawiyata Tamansiswa University in Yogyakarta who had passed capital market courses in both the Accounting and Management Study Programs. The analysis technique used for hypothesis testing is multiple linear regression. The results of this study indicate that capital market socialization has a positive effect on student investment interests in the capital market, while the perception of risk does not significantly influence student investment interests in the capital market.